Contagion, Monsoons, and Domestic Turmoil in Indonesia : A Case Study in the Asian Currency Crisis - Saxena, Sweta; Cerra, Valerie (Washington, D.C. : International Monetary Fund, 2000)
This paper investigates whether Indonesia's recent currency crisis was due to domestic fundamentals, common external shocks ('monsoons'), or contagion from neighboring countries. Markov-switching models attribute speculative pressure on Indonesia's currency to domestic political and financial factors and contagion from speculative pressures in Thailand and Korea. In particular, the results from a time-varying transition probability Markov-switching model (which overcomes some drawbacks of previous methods) show that inclusion of exchange rate pressures from Thailand and Korea in the transition probabilities improves the conditional probabilities of crisis in Indonesia. There is also evidence of contagion in the stock market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet